Herbert McCabe on God and Humanity - Hewitt, Simon (New blackfriars, 2021)
Over the eight hundred years of the English Dominican province, few of its members have matched the rigour and depth of thought of Herbert McCabe. This paper presents a brief overview of McCabe's thought, focusing first on his understanding of God and then on his conception of human beings. Like Thomas before him, McCabe thought it vital to think clearly and correctly about both God and humanity, an effort which in the case of God involves recognising the many ways in which we cannot think of God.